Two forward genetic screens for vein density mutants in sorghum converge on a cytochrome P450 gene in the brassinosteroid pathway. (October 2015) - Rizal, Govinda; Thakur, Vivek; Dionora, Jacqueline; Karki, Shanta; Wanchana, Samart; Acebron, Kelvin; Larazo, Nikki; Garcia, Richard; Mabilangan, Abigail; Montecillo, Florencia; Danila, Florence; Mogul, Reychelle; et al.
Summary The specification of vascular patterning in plants has interested plant biologists for many years. In the last decade a new context has emerged for this interest. Specifically, recent proposals to engineer C4 traits into C3 plants such as rice require an understanding of how the distinctive venation pattern in the leaves of C4 plants is determined. High vein density with Kranz anatomy, whereby photosynthetic cells are arranged in encircling layers around vascular bundles, is one of the major traits that differentiate C4 species from C3 species. To identify genetic factors that specify C4 leaf anatomy, we generated ethyl methanesulfonate‐ and γ‐ray‐mutagenized populations of the C4 species sorghum (Sorghum bicolor), and screened for lines with reduced vein density. Two mutations were identified that conferred low vein density. Both mutations segregated in backcrossed F2 populations as homozygous recessive alleles. Bulk segregant analysis using next‐generation sequencing revealed that, in both cases, the mutant phenotype was associated with mutations in the CYP90D2 gene, which encodes an enzyme in the brassinosteroid biosynthesis pathway. Lack of complementation in allelism tests confirmed this result. These data indicate that the brassinosteroid pathway promotes high vein density in the sorghum leaf, and suggest that differences between C4 and C3 leaf anatomy may arise in part through differential activity of this pathway in the two leaf types.